2008
DOI: 10.1002/jbm.a.31901
|View full text |Cite
|
Sign up to set email alerts
|

In vitro bioactivity of melt‐derived glass 46S6 doped with magnesium

Abstract: Melt-derived glasses in the system SiO(2)-CaO-Na(2)O-P(2)O(5) were synthesized pure or doped with magnesium from 0.4 to 1.2 wt %, for applications as biomaterials in bony surgery. This chemical element has been chosen because of its high physiological interest. Its introduction for different contents in melt derived glasses has never been studied. The bioactivity of glasses was assessed by immersion of the samples in the simulated body fluid solution. Changes in glass surface morphology and composition after i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
50
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 115 publications
(61 citation statements)
references
References 32 publications
(59 reference statements)
11
50
0
Order By: Relevance
“…The SBF solution was prepared by dissolving NaCl, NaHCO 3 , KCl, K 2 HPO 4 ·3H 2 O, MgCl 2 ·6H 2 O, and CaCl 2 in deionized water and buffering with (CH 2 OH) 3 CNH 2 and HCl 6N to obtain a pH value of 7.4 according to Kokubo's technique [140,141]. The ionic composition of this solution is shown in Table 6.…”
Section: Biological Propertiesmentioning
confidence: 99%
“…The SBF solution was prepared by dissolving NaCl, NaHCO 3 , KCl, K 2 HPO 4 ·3H 2 O, MgCl 2 ·6H 2 O, and CaCl 2 in deionized water and buffering with (CH 2 OH) 3 CNH 2 and HCl 6N to obtain a pH value of 7.4 according to Kokubo's technique [140,141]. The ionic composition of this solution is shown in Table 6.…”
Section: Biological Propertiesmentioning
confidence: 99%
“…Previous studies have reported that ion-dissolution products containing Ca and Mg from bioactive glasses and ceramics could stimulate cell proliferation (Dietrich et al 2009;Sader et al 2009). It is believed that the release of Mg ions from corroding Mg alloys should not cause toxicity (local or systemic), and may even have beneficial effects on cell responses, in the relevant local tissue (Staiger et al 2006;Witte et al 2007).…”
mentioning
confidence: 99%
“…Their bioactive character results of their ability to form a hydroxyapatite layer Ca 10 (PO 4 ) 6 (OH) 2 on their surface when they are immersed in a simulated body fluid (SBF) [4-5-6]. The hydroxyapatite is the major inorganic compound of the human bone.…”
mentioning
confidence: 99%